Cover Image. Issue 3 (March 2015) - Trainor, Paul; Johnson, Randy
<x xml:space="preserve">Abstract</x> Cover Photograph: This month's cover shows a multi‐scale Turing pattern created by Jonathan McCabe, a generative artist living in Canberra, Australia. McCabe creates his artwork by computer using algorithms based on work by Alan Turing to model his reaction‐diffusion theory, as described in his landmark paper "The Chemical Basis of Morphogenesis" (Philosophical Transactions of the Royal Society of London. Series B, Biological Sciences, Vol. 237, No. 641 [Aug. 14, 1952], pp. 37‐72.) Though entirely computer generated, the resulting patterns are strikingly reminiscent of structures arising during the development of muticellular organisms.